Climate smart agriculture impact on food and nutrition security in Ethiopia - Teklu, Abyiot; Simane, Belay; Bezabih, Mintewab (Frontiers in Sustainable Food Systems, 2024)
The objective of this study was to analyze how innovations in Climate-smart agriculture (CSA) contribute to improving the food and nutrition security of smallholder households, thereby promoting sustainable food systems. A cross-sectional household survey was conducted among a multi-stage sample of 424 smallholder farmers drawn from five different agroecosystems. To examine households' food and nutrition security, we used food consumption score (FCS) and modified household dietary diversity score (HDDS) in propensity score matching (PSM) and endogenous switching regression (ESR) estimation models. PSM results showed that crop residue management, compost, and agroforestry have a significant effect on improving households' food and nutrition security by 21.3, 13.6, and 16.6 percent, respectively, whereas Soil and water conservation (SWC) has reduced adopters' food security by 12.9 percent. However, the conditional average treatment effect, or ESR result, reveals that households' food and nutrition security has improved as a result of the adoption of crop residue management, compost, SWC, and agroforestry. Although the impact of crop residue management, compost, and agroforestry is positive, the effect of SWC on household food security has been inconclusive. Hence, it is important to upscale the adoption of multiple CSA innovations to improve smallholder household's food security in the face of climate change.